Jail inmates in 2017 - Zeng, Zhen (Prison and Jail Inmates at Midyear, Jail Inmates, 2019)
Presents data on inmates confined in local jails from 2005 to 2017, including population counts and incarceration rates, inmate demographic characteristics and conviction status, admissions, jail capacity, and inmate turnover rates. Findings are based on data from BJS's Annual Survey of Jails and Census of Jail Inmates. Unlike prisons, jails are locally administered correctional facilities that typically house inmates with a sentence of one year or less, inmates pending arraignment, and individuals awaiting trial, conviction, or sentencing.